The Value of Clinical, Laboratory and Brain CT Scan Findings in Methanol Toxicity - Leila Etemad; Amir Ali Moodi Ghalibaf; Ali Sadr; Masoud Pezeshki Rad; Majid Khadem-Rezaiyan; Amir Behforouz; Setareh Azarkar; Asieh Karimani; Hossein Ghaffari; Mohammad Moshiri (ACTA MEDICA IRANICA, 2026)
Methanol poisoning is a severe intoxication that can be fatal. This study aimed to determine the association between clinical and paraclinical findings, particularly brain radiological findings, and the risk of mortality in methanol-poisoned patients. This retrospective cross-sectional study was conducted at the CTD-IRH-MUMS, Mashhad, Iran, from March 2019 to March 2021. Medical and demographic data of adult patients with a confirmed diagnosis of methanol poisoning who had undergone a brain computed tomography (CT) scan were included. A total of 45 methanol-poisoned patients were enrolled in the study, including 36 men (80%) with a mean age of 34.32±13.20 years. Among them, 15 patients (33.3%) had at least one abnormal finding on their brain CT scans. The most frequent finding was diffuse cerebral hemorrhage (n=12, 26.7%), followed by subcortical white matter changes (n=9, 20%), and putaminal hypodensities (n=7, 15.6%). Although abnormal brain CT findings were associated with a higher risk of mortality (OR=4.929, P=0.019), they were not related to any specific type of CT findings. A Glasgow Coma Scale (GCS) score19 breaths/min (OR=2.675, P=0.006), serum creatinine level>1.8 mg/dL (OR=6.258, P=0.009), potassium level>4.3 mEq/L (OR=3.672, P=0.006), glucose level (OR=1.011, P=0.019), bicarbonate level